Pelaksanaan Peraturan Daerah Tata Ruang Kabupaten Gianyar terhadap Pembangunan Fasilitas Pariwisata Sempadan Sungai Ayung - I Kadek Darmayasa; I Putu Gede Seputra; Luh Putu Suryani (Jurnal Konstruksi Hukum, 2021)
Overcoming the negative impacts on the environment and to create good spatial planning. Gianya Regency carries out spatial use control through zoning, licensing, intensive and disintensive spatial planning. This study aims to analyze the arrangements for the development of river border tourism facilities and to find out the implementation of Regional Regulation Number 16 of 2012 concerning the Gianyar Regency Spatial Plan in the construction of tourism facilities. The research method used is empirical legal research. This study chose a location in Banjar Kedewatan Anyar, Kedewatan Village, Ubud District, Gianyar Regency. The results of the analysis show that the regulation of river border tourism facility development in positive law in Indonesia is contained in Law Number 26 of 2007 concerning Spatial Planning. Apart from this Law, river borders are also regulated in Government Regulation Number 26 of 2008 concerning National Spatial Planning. For the sake of harmony with the existing legislation, the Gianyar Regency Region has also made the Gianyar Regency Regional Regulation Number 16 of 2012 concerning the 2012-2032 Regional Spatial Plan which regulates river boundaries in Article 37 Paragraph 2 describes development carried out near River areas that have been given development rules in rural rivers. From the Implementation of Regional Regulation Number 16 of 2012 concerning the Regional Spatial Plan of Gianyar Regency in the construction of tourism facilities it has been going well but it can be seen through calculations calculated by the Head of the Spatial Planning Division that 89% has been implemented well and 11% is still there a deviation.